Preaching Communication in Building the Spirituality of members of the “Persaudaraan Setia Hati Terate” South Lampung Branch - Wasiti, Iqstyar Suci Retno; Syaripuddin, Apun; Budiwiranto, Bambang (UIN Fatmawati Sukarno Bengkulu, 2025)
TThis research is motivated by the importance of da’wah communication in shaping the spirituality of members of the Persaudaraan Setia Hati Terate (PSHT) South Lampung Branch. PSHT members are not only trained in martial arts techniques but also require the strengthening of moral values, discipline, social awareness, and consistency in religious practices. Although organizational activities are conducted regularly, studies on how da’wah communication is implemented to develop and reinforce members’ spirituality remain limited. Therefore, this research aims to describe and analyze effective da’wah communication practices within the PSHT community.This research uses a qualitative descriptive approach with primary data obtained through in-depth interviews, participant observation, and documentation studies. Data analysis was carried out thematically to identify the da'wah communication methods used and their impact on the spirituality of members. The results show that the form of da'wah communication in the PSHT South Lampung Branch is through da'wah communication through oral, verbal, and verbal communication, with the implementation of three main complementary methods: exemplary behavior (Uswatun Hasanah), advice and attention, and reward and punishment. The role models of seniors exemplify moral and spiritual behavior, advice and attention provide guidance and personal empowerment, while rewards and punishments strengthen motivation and spiritual habits. This combination of methods effectively builds and internalizes spiritual values, enabling members to implement discipline, humility, caring, and self-control in their daily lives.